PENGARUH KANGGORO MOTHER CARE TERHADAP KUALITAS TIDUR BAYI DI WILAYAH KERJA UPT PUSKESMAS PANTAI CERMIN KABUPATEN KAMPAR - Marlinawati, Marlinawati; Aifa, Wira Ekdeni; Mardiya, Rizka; Fitria, Nurhidaya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Poor infant sleep quality can impact growth and development. A preliminary survey of 10 mothers at the Pantai Cermin Community Health Center Work Area revealed that all mothers reported that their babies frequently woke up at night and slept less than 8 hours, resulting in fussiness the next day. One effective method to address this problem is Kangaroo Mother Care (KMC). This study aimed to determine the effect of Kangaroo Mother Care on infant sleep quality in the Pantai Cermin Community Health Center Work Area, Kampar Regency. This study used a quantitative quasi-experimental approach with a pre-test and post-test. The population was 155 infants, with a sample size of 28 respondents. Sampling was conducted using a purposive sampling technique. The research instrument was the Brief Screening Questionnaire for Infant Sleep Problems (BISQ). Data were analyzed using the McNemar test. The study found that before the Kangaroo Mother Care method was implemented, 60.7% of babies experienced poor sleep quality. After the Kangaroo Mother Care method was implemented, 75% of babies experienced good sleep quality. There was an effect of Kangaroo Mother Care on infant sleep quality (P=0.002). It is recommended that community health centers (Puskesmas) provide Kangaroo Mother Care education to mothers with infants with sleep problems. KMC can be promoted as a simple, affordable, and effective infant care method to improve infant sleep quality.Keywords : Kangaroo Mother Care, Infant Sleep Quality